(untitled) (Research, Society and Development, 2020)
A bibliometric analysis using the Web of Science database was performed on the green synthesis of nanomaterials published between 2003 and 2017, obtaining a sample with a total of 159 publications. The number of citations of each paper, thematic areas, sources of publication and countries of origin were quantified. The ten most cited papers were described in further detail, listing the precursor materials, the kind of material produced among other characteristics. There is a variety of precursors listed in the literature, including fungi, bacteria, plants, extracts from plants and fruits. Although United States was a pioneer and is influent in this line of research, India is taking the lead due to government incentives and the presence of natural resources having a total of 44.65% of the analyzed works. Silver oxides is the material most produced by this method, according to the most cited works and are commonly applied in antibacterial activity. The main areas of discussion at WoS for this topic are the Chemistry and Science Technology categories with 55 papers each. The main sources of publication are the Colloids and Surfaces B - biointerfaces and RSC Advances with 3,774% in each journal in relation to the study sample. Potentialities of the new nanomaterials production method that could be exploited by other researchers from the use of new precursors, including solid agroindustrial wastes, with the opportunity to add value to the biomass and consequently to reduce environmental impact generated by by-products.